Status of public sector dental health-care services in Nellore District, Andhra Pradesh, India - Chandrasekhara Reddy Vuyyuru; Manickam Ponnaiah; Rajeshree Narayan Rangari (Wolters Kluwer Medknow Publications, 2022)
Background and Objectives: Primary health centers (PHCs) are the foundation of rural health services in India. The nonavailability of reports on the status of dental care services at public health-care centers in rural Andhra Pradesh prompted us to describe the status of dental care services provided at public health-care centers in the Nellore district of Andhra Pradesh. Materials and Methods: This cross-sectional study was conducted using a semi-structured interview guide, based on the Indian Public Health Standards (IPHSs) guidelines. Data were collected on the dental health workforce, equipment, and facilities available, dental care services provided in all government dental care units, and dental care services provided by PHCs without dentists in the Nellore district, from dental and medical doctors, respectively. The descriptive statistics (frequencies) were performed describing the availability of workforce, equipment, and facilities, and the type of dental care services provided. Results: Of 95 public health-care centers in the Nellore district, only 18 centers provided dental care services. No single center was furnished with the prescribed dental health workforce, equipment, and facilities to render comprehensive dental care services to an optimum level according to IPHS guidelines. There were neither oral health promotional activities nor outreach programs targeting rural children, families, and communities carried out at these PHCs as per the IPHS guidelines. Conclusion: An inadequate dental health workforce, deficient dental equipment, and facilities, and very limited dental care services were found at these public health-care centers in the Nellore district, making these services almost nonexistent to rural populations.